Efek Pati Resisten Singkong (Manihot esculenta Crantz) terhadap Indeks HOMA-IR dan HOMA-B Tikus Model Diabetes - Maria Ulfa; Elly Nurus Sakinah; Yohanes Sudarmanto; Jauhar Firdaus (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Insulin resistance is a condition in which target organs fail to respond normally to insulin. Cassava contains 9,69 percent starch that resist to digestive enzyme in intestine and has been shown to increase insulin sensitivity and enhance β cell function. The aim of this study was to analyze the difference effect of native cassava starch and cassava resistant starch consumption on insulin resistance and β cell function indexes. This study was quasy experimental research with post-test only control group design using 16 male wistar strain rats divided into four groups: K1 (normal rats with standard diet), K2 (diabetic rats with standard diet), P1 (diabetic rats with native cassava starch diet) and P2 (diabetic rats with cassava resistant starch diet). The rats were fed with high fat diet and injected with low-dose streptozotocin to mimic the patogenesis of type 2 diabetes. The rats were then fed with assigned diet for 28 days. The data collection was obtained from laboratory examination of fasting plasma glucose and fasting plasma insulin to determine HOMA-IR and HOMA-B indexes. Post Hoc analysis showed no difference in both indexes between native cassava starch and cassava resistant starch fed groups (p>0,05).